Dampak Sosial-Ekonomi PHK terhadap UMKM Ikan Olahan: Studi Kualitatif pada Pelaku Usaha Tradisional - Lathifah Ananda Putri; Najwa Nabila; Ruli Pebrina; Vany Fadillah Bastian (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The micro, small, and medium enterprises (MSMEs) sector plays a vital role in sustaining the national economy, particularly in food security and employment absorption. However, this sector remains highly vulnerable to economic disruptions, including large-scale layoffs in the industrial sector. This study aims to examine the socio-economic impacts of layoffs on the sustainability of traditional fish processing businesses. A descriptive qualitative approach was employed, with data collected through semi-structured interviews with a traditional fish processor who has operated since 1990 in Tanjung Morawa, Deli Serdang, North Sumatra. The findings reveal that layoffs have led to a significant decline in consumer purchasing power, resulting in a drop in daily production volume (from 20 to 5–8 baskets) and increased waste due to unsold inventory. The lack of innovation, absence of adaptive strategies, and minimal external support have further exacerbated the business’s vulnerability. Therefore, policy interventions and capacity-building programs are essential to enhance the resilience of MSMEs amid labor market fluctuations.